2021
DOI: 10.1016/j.htct.2020.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hydroxyurea on cytotoxicity, inflammation and oxidative stress markers in neutrophils of patients with sickle cell anemia: dose-effect relationship

Abstract: Introduction Although the efficacy of hydroxyurea (HU) in inhibiting erythrocyte sickling has been well demonstrated, the action of this drug on human neutrophils and the mechanism by which it improves the manifestations of the disease have not been studied thoroughly. We aimed to investigate the cell viability, along with inflammatory and oxidative markers in the neutrophils of sickle cell anemia (SCA) patients and the effects of HU therapy on these cells, by evaluating the dose-responsiveness. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…23 The effects of HU on the hematological parameters revealed that it could result in higher levels of hemoglobin, hematocrit, and mean corpuscular volume (MCV) and a decline in leukocyte and neutrophil numbers. 24 Further, a significant increase was observed in the activity of the LDH enzyme in the SCA group as compared to the control group. All the HU-treated groups demonstrated a significant decline in LDH levels in comparison to the SCA group.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…23 The effects of HU on the hematological parameters revealed that it could result in higher levels of hemoglobin, hematocrit, and mean corpuscular volume (MCV) and a decline in leukocyte and neutrophil numbers. 24 Further, a significant increase was observed in the activity of the LDH enzyme in the SCA group as compared to the control group. All the HU-treated groups demonstrated a significant decline in LDH levels in comparison to the SCA group.…”
Section: Discussionmentioning
confidence: 84%
“…All the HU-treated groups demonstrated a significant decline in LDH levels in comparison to the SCA group. 24 It was noted that SCA patients had significantly higher leukocyte and neutrophil counts and that HU resulted in not only an increased concentration of HbF but also a decreased number of these cells. 24 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…HCW employment has not been previously reported as a risk factor in SCD ICU admission but has been associated with COVID-19 morbidity in the general US population as well as comprehensive meta-analysis [13] , [14] .. HU use has been reported to reduce morbidity in SCD in one report [1] but not others [10] , [21] . It is biologically plausible that HU might decrease morbidity from COVID-19 infection due to reduction of coagulation and neutrophil and endothelial cell activation [26] , [27] , [28] . Finally, the level of immature granulocytes has not been previously reported as a risk factor in SCD ICU admission, but is associated with disease severity and ICU admission in the general population [15] , [17] .…”
Section: Discussionmentioning
confidence: 99%